Characterizing the Role of Glutamine synthetase Gene on Ammonia Nitrogen Detoxification Metabolism of the Razor Clam Sinonovacula constricta - Sun, Gaigai; Sun, Changsen; He, Jing; Yao, Hanhan; Dai, Wenfang; Lin, Zhihua; Dong, Yinghui (Frontiers in Marine Science, 2021)
Ammonia nitrogen is a common toxic substance in the aquatic system, which seriously threatens the survival and growth of clams. However, little is known about the ammonia metabolism and detoxification strategy in razor clam. In the present study, the polymorphism of glutamine synthetase gene from Sinonvacula constricta (Sc-GS) was found to be related to ammonia tolerance. By comparing the CDS region of Sc-GS from two geographical populations, a total of 14 and 12 single nucleotide polymorphisms (SNPs) were identified, respectively, of which ten loci were shared between two populations. Among them, the locus c.1133T > G exhibited an extremely significant and strong association with ammonia tolerance in both populations (P < 0.01) and the locus c.1133T > G was missense mutation, which led to the amino acid change from leucine (Leu) to arginine (Arg). Further, the results about hematoxylin-eosin (HE) staining and immunohistochemistry of Sc-GS protein in gills and hepatopancreas were found that it was specifically localized in the lateral cilia of gill filaments and the endothelial cells of hepatocytes. After inhibiting Sc-GS expression by RNA interference (RNAi) technology, the transcript levels of Sc-GS were extremely significantly down-regulated at 24, 48, 72 and 96 h (P < 0.01) in the hepatopancreas. Taken together, these results indicated that Sc-GS gene may participate in ammonia metabolism. In addition, these results will help to demonstrate the role of Sc-GS in ammonia nitrogen metabolism and provide markers related to ammonia nitrogen tolerance for molecular marker-assisted selection of the razor clam.